PENERIMAAN PAJAK DAERAH MELALUI KONTRIBUSI PAJAK HOTEL DAN HIBURAN - Deden Edwar Yokeu Bernardin; Iwan Sofyan (Jurusan Akuntansi Politeknik Negeri Bandung, 2017)
Abstract: The purpose of this study to determine the local taxes revenue through the contribution of hotel taxes and entertainment taxes revenue area of Bandung city period 2010-2015. The method of analysis used in the research is descriptive method verifikatif with quantitative approach. The result of hotel tax contribution and entertainment to tax revenue does not reach 50% because that becomes the local tax eye reaching 11 item of tax and from both taxes studied as independent variable of highest contribution value is hotel tax. Hotel tax has a significant influence with the positive direction of local tax revenues of local tax revenues of Bandung, it shows the contribution of hotel taxes very meaningful value. The entertainment tax has a negative and insignificant effect on local tax revenues, which means that if the entertainment tax increases then local tax revenues do not increase directly, local tax revenues may remain or may decrease. The influence of hotel tax and entertainment tax on local tax revenues simultaneously have a significant influence with the positive direction. This simultaneous influence indicates that the effect of hotel and entertainment taxes should be done together to have an impact on changes in local tax revenues. Keywords: Hotel Taxes, Entertainment Taxes, Local Taxes